Determınation of the Opinions and Expectations of Nursing Students About Clinical Nurses - Münevver Sönmez; Öznur Gürlek Kısacık (Association of Nurse Managers, 2020)
INTRODUCTION: The aim of this study was to evaluate the opinions and the expectations of nursing students about clinical nurses METHODS: This descriptive research was carried out in the Nursing department of a public university. Sample selection and 68.7% of the universe has been reached. The data were collected by using the related literature with the 'Questionnaire Form' created by the researchers. RESULTS: The nursing students stated that the nurses could not allocate sufficient time for them because of their workload (49.0%) and the high number of students (53.0%). In addition, it was determined in the study that nurses saw students as people who reduced their workload (60.1%) and nurses expected students to do non-patient jobs in the clinic (51.0%). DISCUSSION AND CONCLUSION: In the study, it was determined that the nurses were insufficient to be the right role models for the nursing students.